A Review on Concept and Determination of Training and Education Program Requirements in Human Management - Abang Mohd. Razif Abang Muis (Human Resource Management Academic Research Society, 2023)
This article aims to identify the concept and determination of training and education program requirements in human management based on existing works. This article also aims to analyse the concept and determination of training and education program requirements in human management based on existing works. The questions that arise are what is the concept of training and education programs in human management? What are the determinants of the need for training and education programs in management? In general, there have been many efforts of training and education programs that try to improve the quality of employees in an organization. Therefore, this article tries to examine these questions based on secondary sources. It thus forms a mapping work on the concept and determination of training and education program requirements in human management.